VARIASI SUHU DAN WAKTU EKSTRAKSI TERHADAP KUALITAS PEKTIN DARI KULIT PISANG TANDUK - Dorti Desmawarni; Farida Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimed to get the best extraction of time and temperature on the quality of pectin from banana peels horn. This research used a Completely Randomized Design (CRD) with two factors treatments and three replications. First factor the extraction of temperature is T1 (80°C) and T2 (90°C). Second factor the extraction of time is W1 (60 minutes), W2 (70 minutes) and W3 (80 minutes). Parameters measured were yield pectin, moisture content, ash content, methoxyl content, time of jelly, organoleptic assessment descriptively of  pectin colour and pectin jelly. The value of observation were analyzed using Analysis of Varians (ANOVA) followed by Duncan’s New Multiple Range Test (DNMRT) on 5% level. The results showed that the interaction between temperature and extraction of time was significants (P<0.05) the water content, methoxyl content and the time of the formation of jelly. Extraction of temperature significants different (P<0.05) on yield, moisture content, ash content, methoxyl, and time of jelly. Extraction  of time was significants (P <0.05), the yield of pectin, moisture content, ash content, methoxyl content, and time of jelly. Based on organoleptic assessment descriptive (colour) of the pectin and jelly is brown and be dark brown with the increase in the temperature and the extraction of time. The best treatment of pectin is extraction of temperature (90°C) and the extraction of time (80 minutes). Keywords: Extraction of temperature, extraction of time, pectin.